Increasing Students' Interest in Learning Fiqh Subjects through the Picture and Picture Learning Model at MIN 14 Pidie Jaya - Misnaiyah; Mauliza, Miftahul (MANDAILING GLOBAL EDUKASIA, 2025)
The achievement of learning objectives must also be supported by the selection of learning methods and models. A teacher must choose the right model so that the teaching and learning process is more effective and efficient. However, in reality at MIN 14 Pidie Jaya, teachers are still less precise in choosing models, therefore the teaching and learning process becomes a saturated and less active atmosphere. The learning model applied in this learning is the Picture and Picture model. The Picture and Picture model is one of the steps that can be taken to improve and increase students' interest in learning. This learning model is one of the models that uses paired images and is sorted into a logical sequence. The problems in this study are (1) How are the teacher's activities in learning Fiqh by applying the Picture and Picture model (2) How are the students' activities in learning Fiqh by applying the Picture and Picture model and (3) How is the students' interest in learning Fiqh by applying the Picture and Picture model? This study includes Classroom Action Research which is carried out in three cycles. Each cycle consists of four stages, namely design, implementation, observation, and reflection. The subjects in this study were 19 students in class II of MIN 14 Pidie Jaya. The research data were obtained using teacher and student observation sheets and student test results, then this data was analyzed using a percentage formula. The research results obtained were (1) teacher activity in cycle I using the Picture and Picture model cycle I from 70.36% cycle II to 81.53% and in cycle III to 98.46%, (2) student activity in cycle I using the Picture and Picture model cycle I 72.30% cycle II to 76.92% and in cycle III to 96.92% and (3) student interest in learning Fiqh in cycle I using the Picture and Picture model 61.11% cycle II to 77.77% and in cycle III to 94.44%. This shows that the interest in learning Fiqh on the material of the provisions of obligatory prayer using the Picture and Picture model shows Very Good results. Based on the results of this study, it can be concluded that the application of the Picture and Picture model can increase student interest in learning to be more active and teacher abilities can improve to be better.